1995
DOI: 10.2307/2077739
|View full text |Cite
|
Sign up to set email alerts
|

The Capital Crunch: Neither a Borrower nor a Lender Be

Abstract: The dramatic reduction in the growth rate of bank lending associated with the 1990-91 recession, particularly in New England, has evoked claims by many observers of a credit crunch. However, because of the difficulty in determining whether the observed slow credit growth is a demand or supply phenomenon, convincing evidence of the practical importance of credit crunches for economic activity remains elusive. We overcome this obstacle by examining a cross-section of banks in New England that have experienced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
263
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(286 citation statements)
references
References 6 publications
21
263
0
2
Order By: Relevance
“…Estrella (2004), Lindquist (2004), and Micco and Panizza (2006) analyzed the lending behavior of banks according to business cycle to explain the procyclicality of banks. Peek and Rosengren (1995) and Gambacorta and Mistrulli (2004) argued that low-capitalized banks are forced to cut their loan supply during a recession. Thus, they suggested that the banks having weak capital adequacy are procyclical to business cycle fluctuation.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Estrella (2004), Lindquist (2004), and Micco and Panizza (2006) analyzed the lending behavior of banks according to business cycle to explain the procyclicality of banks. Peek and Rosengren (1995) and Gambacorta and Mistrulli (2004) argued that low-capitalized banks are forced to cut their loan supply during a recession. Thus, they suggested that the banks having weak capital adequacy are procyclical to business cycle fluctuation.…”
Section: Related Literaturementioning
confidence: 99%
“…In particular, Berger and Udell (1994), Peek and Rosengren (1995), Hancock, Laing and Wilcox (1995), Shrieves and Dahl (1995), and Wagster (1999) thought a low BIS ratio of banks as proxy of capital adequacy has made government supervisors strengthen regulations, which results in a negative impact on loan to SMEs.…”
Section: Related Literaturementioning
confidence: 99%
“…Additional evidence showing that banks do reduce lending to riskier companies in an effort to control capital levels on their balance sheets have also been presented by Dahl and Shrieves (1990), Peek and Rosengren (1997) and Jacques and Nigro (1997).…”
mentioning
confidence: 83%
“…A major implication of their findings is that the financial situation of the banking sector should be taken into account by the monetary policymakers. In a third paper, Peek and Rosengren (1995c), in order to limit the effect of the loan demand shocks, adopt an interesting approach that consists in focusing on deposits (liabilities) rather than loans (assets) to test the capital crunch hypothesis. The authors find evidence of a capital crunch by obtaining a strong positive relationship between a bank's capital shock and the growth rate of its deposits.…”
Section: Literature Reviewmentioning
confidence: 99%